2017
DOI: 10.1515/amm-2017-0011
|View full text |Cite
|
Sign up to set email alerts
|

FEM Analysis of Loads and Torque in a Skew Rolling Process for Producing Axisymmetric Parts

Abstract: Skew rolling is a metal forming technique which can be used for producing stepped axles and shafts. This paper investigates seventeen cases of rolling at varying process parameters by the finite element method. As a result, it is possible to determine the effect of the forming angle α, skew angle Θ, linear velocity of the chuck, v, billet temperature, T, rotational speed of the rolls, n, reduction ratio, δ and friction factor, m, on axial load (acting on the chuck), radial load (acting on the roll in the radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…Preliminary numerical analyses performed by Xu and Shu [2] and Pater et al [10] have shown that this method can be effectively used to produce axles, both solid and hollow. As it was demonstrated by Pater [11], the skew rolling process requires relatively low loads and torques. An enormous advantage of skew rolling is the fact that the same set of tools (tapered rolls) can be used to produce parts of different shapes [12,13].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Preliminary numerical analyses performed by Xu and Shu [2] and Pater et al [10] have shown that this method can be effectively used to produce axles, both solid and hollow. As it was demonstrated by Pater [11], the skew rolling process requires relatively low loads and torques. An enormous advantage of skew rolling is the fact that the same set of tools (tapered rolls) can be used to produce parts of different shapes [12,13].…”
Section: Introductionmentioning
confidence: 92%
“…After that, the rolls are re-started and the chuck is set in translational motion. This marks the beginning of Operation 2 which is performed as a standard CNC skew rolling process [2,[10][11][12][13]. According to the proposed solution, the chuck moves with a constant linear velocity v C = 50 mm/s, while the velocity of the radially moving rolls is selected such to ensure that products have the required shape.…”
Section: Numerical Model Of the Skew Rolling Process For Rail Car Axlesmentioning
confidence: 99%
“…Wstępne symulacje numeryczne [2,3] pokazały, że tą metodą można skutecznie wytwarzać osie wagonowe -zarówno pełne, jak i drążone. Jak wykazano przy tym w pracy [4], proces walcowania skośnego wymaga zastosowania stosunkowo niewielkich sił i momentów. Ogromną zaletą walcowania skośnego jest także możliwość stosowania tych samych narzędzi (rolek stożkowych) do wytwarzania wyrobów o różnych kształtach [5,6].…”
Section: Wprowadzenieunclassified
“…В работе [12] рассмотрены особенности износа валков и оправок прошивного стана с применением компьютерного моделирования. Кроме анализа энергосиловых параметров [13] и особенностей формоизменения, компьютерное моделирование также применяют для предсказания разрушения во время деформации [14] и формирования микроструктуры [15].…”
Section: Doi: 1017073/0368-0797-2020-10-848-855unclassified